Social enterprise and policy discourse: a comparative analysis of the United Kingdom and Australia. (19th October 2018) - Mason, Chris; Moran, Michael
Abstract : This article analyses social enterprise policy in the United Kingdom and Australia, comparing the different ideational strategies adopted by policymakers in each country. Drawing upon a unique policy dataset, it reveals that in the United Kingdom policymakers combined several ideas into a sophisticated narrative that sought to reflect sector growth and engage more deeply with the public. In comparison, Australian policy actors focused on a single idea, which underlined a more pragmatic approach to the utilisation of policy narratives. Through this analysis, the article makes a number of contributions. Empirically, it provides the first comparative examination of the interplay between ideas and rhetoric in the field of social enterprise policy. Theoretically, it demonstrates the utility of discursive institutionalism in the field of policy analysis, and develops its analytical leverage by identifying the different strategies available to policymakers.